Eye feel you : a project inspired by colour blindness perception - Lam, Jayne Jan Wen (2018)
Colours have the ability to evoke certain emotions in all of us. This is the same for those who are colour blind as well. Being colour blind does not necessarily mean that one cannot see colours at all, it just means that the colours they see are different from the ones most people see. And despite our differing visual perspectives, we experience colour in similar ways. Colour vision deficiency is a norm in my family and yet none of them sees it as a disadvantage or considers it a disability. My father is the closest relative I have with this condition. Eye Feel You tackles colour vision deficiency from his viewpoint. The interactive installation invites you to experience how a colour triggers emotions which are translated into a tactile form.